From Basic Tourism Products to a Comprehensive Offer of a Tourism Area - Panasiuk, Aleksander (Regional Barometer. Analyses & Prognoses, 2017)
This study is an attempt to analyze the evolution of terminology used in tourism sciences concerning a tourism product as well as derivative terms. The issue of a tourism product causes a lot of controversy over its semantics and structure in both international and domestic literature on the subject. The problem mainly arises from use of this term by representatives of many sciences and the industry. Moreover, the issue of a tourism product is constantly being developed in terms of both theoretical and pragmatic aspects. The objective of the study is to outline applied terms which include the category of a tourism product as well as to propose a concept of a comprehensive tourism offer of an area which is made up by particular components. The article is mainly theoretical; however, the discussed issues are of a utilitarian nature. They use the method of critical analysis of literature, logic operations and heuristics. Taken considerations are original aspects. The result of the study is to design a concept of a comprehensive offer of a tourist area.